Falling down the rabbit hole: an introspective self-portrait - La, Jasmine (My University, 2023)
The purpose of this arts-based learning project is to link personal perception of self to theories and ethics studied throughout the Child and Youth Care Program. Within the self-reflective project the topics explored include: relational ontology, paradigms and life positionings, theoretical frameworks, and finally ethical frameworks. In participating, self-discovery and professional praxis were the focal points of the project. Part of this reflection relates to the characteristics of a relational Child and Youth Care approach; Being, Interpreting, and Doing (BID). Reflecting on how child and youth care practitioners function in supporting roles within the community. The project connects all aspects of course content, personal and professional experiences, interwoven into a metaphorical representation of self. There’s many layers represented when viewing my art piece. The process in doing this required the willingness to allow oneself to succumb to vulnerability in order to intentionally understand oneself. Connecting many metaphors throughout my lifespan which highlights my understanding of self through multiple lenses relating to the child and youth care practice.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: arts-based learning; self-portraits; child and youth care practice